PHYSICAL, SENSORY, AND MICROBIOLOGICAL CHARACTERISTICS OF STEVIA-BASED LIQUID SUGAR ENHANCED WITH CINNAMON EXTRACT - Verdini, Liana; Kalsum, Nurbani; Zukryandry (Jurnal Teknologi Pertanian, 2026)
Public health awareness is driving the increased demand for natural, low-calorie food products. This study aimed to evaluate the effect of stevia and cinnamon ratios on the physical, sensory, and microbiological characteristics of liquid sugar, as well as to identify the optimum formulation. Stevia extraction was conducted using a water-based heating method, while cinnamon was extracted using sonication. Results showed that increasing the proportion of cinnamon significantly elevated pH values (5.84 to 6.61), total dissolved solids (2.96 to 5.96 °Brix), viscosity (0.87 to 2.33 cP), and colour lightness (L*) of the formulated liquid sugar. All formulations were microbiologically safe, with Total Plate Count (TPC) <1 CFU/mL and negative results for E. coli. The F1 formulation (2 grams of stevia : 1 gram of cinnamon) was identified as the best treatment, providing an optimal balance between physical stability and sensory acceptance, particularly for the aroma attribute (score 5.25). This combination produces a stable functional sweetener, although cinnamon usage must be controlled to prevent bitterness from polyphenol compounds.